Purchase intention of Millennial Muslims toward B2C e-commerce - Nur Rizqi Febriandika; Luthfiyatillah; Syed Marwan Mujahid bin Syed Azman (Innovative Marketing)
Indonesia’s e-commerce market, particularly B2C, continues to expand, attracting both domestic and foreign investments. Despite this growth, a notable decline in B2C sales occurred. This drop is largely attributed to rising competition in the market, which has made it increasingly difficult for platforms to retain consumer interest. This study investigates the factors that influence Millennial Muslim consumers’ purchase intentions on B2C e-commerce in Indonesia using structural equation modeling. The respondents in this study were taken from the Millennial generation of e-commerce users. This generation was chosen because they are economically more established than Generation Z and in terms of technology use, are more expert than Baby Boomers. Initially, 700 responses were collected, but after excluding incomplete or non-qualifying data, 434 valid responses were analyzed. The findings reveal that perceived risk (β: 0.206), perceived quality (β: 0.440), and enduring involvement (β: 0.240) positively affect perceived trust, whereas situational involvement (β: -0.331) has a negative impact. Additionally, enduring involvement (β: 0.659), situational involvement (β: 0.133), and perceived trust (β: 0.103) were found to positively influence purchase intention, while perceived risk (β: -0.093) negatively affects it. The study emphasizes that enduring involvement (β: 0.659) is the strongest variable that increase purchase intention in B2C e-commerce. Enduring involvement refers to a consumer’s long-term interest and engagement with a product category, driven by personal relevance, values, or consistent motivations. AcknowledgmentThe authors would like to thank the Research and Innovation Institute (LRI), Universitas Muhammadiyah Surakarta, for the enormous financial support in writing this study through the funding scheme of the 2025 Outstanding Research of Study Program (RU-PRODI).